Real-Time Substructure Tests and Numerical Simulation of Mechanical Characteristics of Natural Rubber-Laminated Bearings - Peng, T.B.; Ni, Y.H.; Wu, Y.C. (Проблемы прочности, 2018)
Natural rubber lamination is a kind of seismic isolation of bearings often used in civil engineering. The advantage of laminated bearings is large vertical stiffness and small lateral stiffness. In seismic regions, structural periods would be extended and the effect of seismic forces can be lowered using bearings. In previous tests, the static cyclic loading method was mainly used that failed to take account of the loading rate. The real-time substructure testing is proposed to simulate true seismic loads. This testing and test setup were first introduced, and the effect of the loading rate was studied. Then the effects of vertical pressure and peak acceleration of ground motion were studied. At last the test results were simulated by the finite element method, and an accurate method to calculate seismic responses of bridges with laminated bearings was proposed.